Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3892/etm.2021.10234
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in systemic lupus erythematosus: A case‑control study

Abstract: Sleep disturbances in systemic lupus erythematosus (SLE) are not well understood. The restless legs syndrome (RLS) is one of the frequent occurring sleep disturbances in SLE. The aim of this study was to evaluate the prevalence of RLS and its characteristics in SLE. We evaluated, in a prospective case-control study, 26 patients with SLE and 26 patients without SLE in an age-and sex-matched control group. An RLS-positive diagnosis met International RLS Study Group (IRLSSG) criteria. We used standardized questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
4
0
3
Order By: Relevance
“…A 2015 Turkish study showed that RLS is more common in patients with SLE than in the general population (30.6% vs. 4.3%), especially when accompanied by iron deficiency anemia [ 21 ]. Similar results were achieved in a 2018 U.S. study (34% vs. 10%) and a 2021 Romanian study (34.2% vs. 7.69%) [ 22 , 23 ]. It is speculated that in genetically susceptible patients, antibodies against cells responsible for dopaminergic signaling in the central nervous system may play a predominant role in the coincidence of RLS with SLE [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…A 2015 Turkish study showed that RLS is more common in patients with SLE than in the general population (30.6% vs. 4.3%), especially when accompanied by iron deficiency anemia [ 21 ]. Similar results were achieved in a 2018 U.S. study (34% vs. 10%) and a 2021 Romanian study (34.2% vs. 7.69%) [ 22 , 23 ]. It is speculated that in genetically susceptible patients, antibodies against cells responsible for dopaminergic signaling in the central nervous system may play a predominant role in the coincidence of RLS with SLE [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…Elevated levels of IFN-α autoantibodies have been shown to have a protective effect in SLE, thereby capable of lowering disease severity 23 , 38 , 39 . Several smaller studies have found that the prevalence of RLS is higher in SLE patients than in controls 40 42 , although whether they are caused by a common pathophysiological pathway involving IFN-α is unknown. A case report by LaRochelle and Karp 43 documented a patient that developed RLS after IFN-α therapy for chronic hepatitis C. Between 50 and 75% of patients treated with recombinant IFN-α develop anti-interferon antibodies 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Системная красная волчанка. Как и в случае с РА, распространенность СБН у пациентов с СКВ значительно выше, чем в общей популяции -30,6-37,5 % [40][41][42]. По сравнению с контрольной группой, пациенты набирали значительно больше баллов по шкале тяжести IRLS [41,42].…”
Section: синдром беспокойных ног и анемия хронического воспаленияunclassified
“…Как и в случае с РА, распространенность СБН у пациентов с СКВ значительно выше, чем в общей популяции -30,6-37,5 % [40][41][42]. По сравнению с контрольной группой, пациенты набирали значительно больше баллов по шкале тяжести IRLS [41,42]. Более того, даже в группе пациентов наблюдалась определенная неоднородность: при наличии анемии (ЖДА, АХЗ) СБН встречался чаще, и тяжесть его была выше, чем у пациентов с СКВ без анемии.…”
Section: синдром беспокойных ног и анемия хронического воспаленияunclassified
See 1 more Smart Citation